Effects of Yogic Practices on Different Systems of Human Body: The impact of Yogic practices on human body and blood sugar levels (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The study reveals that there is significant reduction in post-testcondition. Yogic exercises showed a positive and significant impact on diabeticadults. In the case of systolic blood pressure, diastolic blood pressure it wasfound that the reduction level was significant in post-test condition. Similarstudy is necessary to observe the efficacy Asanas and Pranayama on differentage level and gender. Another suggestion may also be that these variablesshould be included with other variables and different time intervals with anorganized manner. The increased sensitivity seems to be sustained for long timeresulting in a progressive long term effect of Asanas. The study is significantbecause, it has for the first time attempted to probe the mechanism by whichyoga- Asanas reduce blood sugar. In the present study there was a significantfall in the fasting blood glucose levels in the yoga group. All theparticipants in the yoga group develop a sense of wellbeing without any sideeffect. So they are self-motivated to continue the yoga practice as a dailyroutine in their life.